1988
DOI: 10.1161/01.cir.78.3.506
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training in patients with severe left ventricular dysfunction. Hemodynamic and metabolic effects.

Abstract: We studied the effects of exercise training in patients with chronic heart failure attributed to left ventricular dysfunction (ejection fraction, 24 ± 10%). Twelve ambulatory patients with stable symptoms underwent 4-6 months of conditioning by exercising 4.1 ± 0.6 hr/wk at a heart rate corresponding to 75% of peak oxygen consumption. Before and after training, patients underwent maximal bicycle exercise testing with direct measurement of central hemodynamic, leg blood flow, and metabolic responses. Exercise t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
314
6
17

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 618 publications
(374 citation statements)
references
References 37 publications
34
314
6
17
Order By: Relevance
“…More specifically, the positive impacts of exercise training in these patients have been correlated to central and peripheral hemodynamics, ventilatory and metabolic responses, and the symptomatic status (63)(64)(65)(66). Enhancements in the sympathetic response, autonomic heart rate control and variability have also been noticed (67).…”
Section: Impact Of Exercise Trainingmentioning
confidence: 97%
“…More specifically, the positive impacts of exercise training in these patients have been correlated to central and peripheral hemodynamics, ventilatory and metabolic responses, and the symptomatic status (63)(64)(65)(66). Enhancements in the sympathetic response, autonomic heart rate control and variability have also been noticed (67).…”
Section: Impact Of Exercise Trainingmentioning
confidence: 97%
“…Theoretically, the most profound effect of exercise training is expected to be on E a , given that several lines of evidence support that exercise training shows its favorable effects on peak VO 2 improvement principally by peripheral adaptations 27. Indeed, it has been shown that exercise training induces significant improvements in arterial compliance,28 peripheral resistance,29 wave reflections,30 skeletal muscle oxidative function,31, 32 and arterial‐venous O 2 difference 33. The modest change in E a in our cohort may be caused by the limited time duration of cardiopulmonary exercise intervention.…”
Section: Discussionmentioning
confidence: 99%
“…[35] в программу кардиореабилитации была включена группа больных ХСН II и III функциональ-ных классов [36].…”
Section: о б з о р ыunclassified